English remote teaching in the Amazon during the covid-19 pandemic: “Inglês no campus” experience report - Pereira Diniz, Fernanda; Koei Itikawa Tanaka, Elder; Schwade de Jesus Oliveira, Katia Lais; Piovezan Ferro, Paola; Barros de Souza Hall, Silvia Cristina (Guará Journal, 2022)
This  article  reports  the  experience  in  the  extension project  “In-glês  no  Campus”  which  had  as  its  main goal  to  provide  a  mini-course  in  basic  English  whilst in  remote  learning  environments.  Among  the theoretical  basis  of  the  project  are  the  Communicative Approach, Task-Based Language Learning, Freirean Critical Pedagogy, and Integrated Language and Content Learning. The project  team  members  were three  professors  and  nine  volunteer  undergraduates from  the  Federal  University  of  Western  Pará (UFOPA) English Program. Analysis of the data revealed that the students  were  satisfied  with  the minicourse  of  basic  English.  Simultaneously, the theoretical-practical experiences related to remote teaching were well-received by the volunteers, which had a reflective attitude about the teaching and learning of the English language. Therefore, the execution of the extension project pre-sented important challenges related to teaching and learning in a  remote environment  during  the  pandemic,  and  it  also contributed to the initial education of the English teachers, especially in reference to the use of digital technologies in teaching.
Keywords: English teaching; English as an additional language; Remote teaching; Extension Project; COVID-19